2016
DOI: 10.1002/ctpp.201500088
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Complex Plasmas: Ion Susceptibility for a Partially Ionized Plasma in Parallel Electric and Magnetic Fields

Abstract: The density response function for streaming ions in homogeneous, parallel electric and magnetic fields is derived self-consistently from kinetic theory. Ion-neutral collisions are treated with the Bhatnagar-GrossKrook collision operator assuming a constant ion-neutral collision frequency. The result accounts for the nonMaxwellian distribution function of the ions and is valid in the full range from weak to strong magnetization. It provides the basis for various linear response calculations in the context of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Our results have inspired other researchers in wider fields beyond plasma physics [64][65][66][67][68][69][70][71][72][73][74][75][76]. The followings are examples.…”
Section: Summary and Subsequent Developmentsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results have inspired other researchers in wider fields beyond plasma physics [64][65][66][67][68][69][70][71][72][73][74][75][76]. The followings are examples.…”
Section: Summary and Subsequent Developmentsupporting
confidence: 68%
“…They reported that the turbulence was able to occur at a low Reynolds number if the Weissenberg number was high. Kähler et al derived the ion susceptibility in a partially ionized plasma [65]. Tadsen et al reported that the dust cloud confined in a magnetized plasma was diamagnetic [66].…”
Section: Summary and Subsequent Developmentmentioning
confidence: 99%
“…We expect that our results will also be of direct relevance for experiments. Finally, an interesting question of current interest is how wake effects are modified in a magnetic field, where experiments 33 and linear response simulations 34,35 have observed a drastic modification of the wake potential with increasing field strength.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While the Coulomb interaction of dust with magnetised ions has been previously studied [13][14][15][16] , particularly in the context of wake effects, there are no known theoretical models by which the momentum transfer associated with this interaction may be calculated. However, the similar problem of Coulomb scattering of a point charge in strong magnetic fields has been treated in the context of ion stopping in a magnetised electron plasma, for which Nersisyan, Toepffer, and Zwicknagel have calculated the energy loss of a charge by treating its binary collision with another charge as a perturbation to its helical motion [17][18][19] .…”
Section: Magnetised Deflectionmentioning
confidence: 99%